The Innovational Development In Uzbekistan And Its Pragmatic Essence - qizi, Bahodirova Feruza Bahodir (The journal of contemporary issues in business and government, 2021)
In the following article the pragmatical essence of the opportunities and the conditions created for the reforms implemented in the Republic of Uzbekistan which is undergoing rapid changes, the development of small enterprises and businesses, reforms in the sphere of education, discoveries in the scientific and technical spheres are analyzed based on the recent available data.